Customer Information System performance evaluation of Public Utilities provided by Municipalities - Hernández y Orduña, María Graciela; Lagunes Gómez, Isabel (Revista General de Información y Documentación, 2020)
We conduct a documentary review in scientific and technical search engines and repositories to know the demands of an ever younger and more digitized society, more demanding and with higher expectations regarding the quality of Public Utilities (PU) that must be provided by the State. We conclude that using Customer Information System (CIS) is an effective strategy for identifying areas of opportunity to improve local government management. From the state of the art we identify the need for information that promotes Evidence-based practice (EBP), so we present a CIS prototype to Performance appraisal of 3 PU in real time (public safety, public lighting, and maintaining our parks and public spaces). This prototype is an application software, developed on web platform using technologies: MVC pattern, PHP and JavaScript languages, Bootstrap style sheet framework, and standard for JSon and HTML5 data exchange. The CIS knowledge base combines a survey for the evaluation of quality and an algorithm for evaluating responses and processing them to calculate the average per item and PU. The methodological approach used is the analysis of the expected and perceived quality, from the subjective vision of the external client, through satisfaction surveys applied to PU for provision and procedures.